SUSTAINABLE ECO-TOURISM DEVELOPMENT STRATEGY AS TOURISM ALTERNATIVE DURING COVID 19 PANDEMIC IN POSONG TOURISM AREA - Amin Kiswantoro; Hendra Rohman; Dwiyono Rudi Susanto; Lilik Edi Saputro; Nur Rohman Nur Rohman (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
Abstrack: Posong is a tourist destination that needs to be built, developed, and perfected. Therefore we need right way to develop Posong area into a leading and attractive destination for tourists. Attraction characteristic of Posong's natural attractions is view sunrise and display of seven mountain peaks. Spread plantation land does not forget to be allure Posong's natural tourist destination. However, this potential has not been managed optimally, such as lack of adequate facilities, less intensive promotions, and accessibility problems in form roads are still steep and rocky. In addition, during this pandemic, natural tourism in Posong experienced a decrease in number tourists, which affected local economy. Therefore we need the right strategy to make Posong a sustainable tourism.Purpose: This study aims to analyze ecotourism in Posong tourism sites, Temanggung Regency. Determine and describe economic influence, social influences, environmental influences in Posong tourism destinations, Temanggung Regency before and after ecotourism development strategy.Research methods: Qualitative with explorative. Data collection by observation and documentation.Results and discussions: Strategies used to develop Posong tourist destinations which include application of sustainable tourism principles, ecotourism development, acessibility, and amenity development, Human Resources Development local communities, formation of Posong tourism area managers.Conclusion: Aspects of attractions, environment, and visitors are good and ready to deal with revenge tourism during a pandemic by paying attention to strict health protocols. Sustainable development has a comprehensive, integrated, and human oriented approach